2017
DOI: 10.1093/ons/opx028
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine Green Videoangiography for Surgery of a Ruptured Dissecting Aneurysm in the Precommunicating Anterior Cerebral Artery: A Technical Case Report

Abstract: Preclipping ICG-VA may enhance the advantage of direct surgery for dissecting aneurysm by allowing visualization of the extent of the dissected vascular wall and the related branching arteries. ICG-VA can be an indispensable adjunct to minimize the compromise from the surgical treatment for intracranial dissecting aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…They concluded that ICG videoangiography was able to visualize, during the surgical procedure, the small perforating arteries that cannot be detected by intraoperative DSA (31). In addition, Nagai et al (32) reported a rare case of a ruptured dissecting aneurysm in the A1 segment. Using ICG, the lateral and medial groups of the basal perforating arteries of the anterior communicating artery complex of the ACA were identified prior to clipping, thereby minimizing the risk of complications related to occluding perforator vessels.…”
Section: Current Applicationsmentioning
confidence: 99%
“…They concluded that ICG videoangiography was able to visualize, during the surgical procedure, the small perforating arteries that cannot be detected by intraoperative DSA (31). In addition, Nagai et al (32) reported a rare case of a ruptured dissecting aneurysm in the A1 segment. Using ICG, the lateral and medial groups of the basal perforating arteries of the anterior communicating artery complex of the ACA were identified prior to clipping, thereby minimizing the risk of complications related to occluding perforator vessels.…”
Section: Current Applicationsmentioning
confidence: 99%